Peran Kredit Usaha Rakyat (KUR) dalam Meningkatkan Kinerja UMKM di Kabupaten Pinrang - Rachmatul Hidayat; Rahmat Rahim; Pidiya Alirman; Citra Ayu Ningsih; Bahruddin Bahruddin (Journal of Innovative and Creativity, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a vital pillar of regional economic development by contributing to employment creation, income distribution, and local economic resilience. In Pinrang Regency, MSMEs play a strategic role in supporting community livelihoods; however, their growth potential is often constrained by limited access to formal financing. To address this issue, the Government of Indonesia introduced the People’s Business Credit (Kredit Usaha Rakyat/KUR) program as a policy instrument aimed at expanding affordable and inclusive financing for MSMEs through interest subsidies and simplified credit schemes. This study aims to analyze the role of the KUR program in improving the performance of MSMEs in Pinrang Regency. The research employs a descriptive qualitative approach, utilizing secondary data obtained from the Central Statistics Agency (BPS), Bank Indonesia (BI), the Financial Services Authority (OJK), and relevant prior studies. The findings indicate that KUR has a positive impact on MSME development, particularly in enhancing access to working capital, increasing production capacity, and improving business revenues. MSMEs receiving KUR financing show greater flexibility in business expansion and improved resilience in facing economic challenges. Nevertheless, the effectiveness of the KUR program is not yet optimal. Several obstacles persist, including low levels of financial literacy among MSME actors, limited business assistance and mentoring, and insufficient digital readiness to adapt to technological and market changes. These challenges reduce the overall impact of credit utilization on long-term business sustainability. Therefore, stronger policy synergy is required between local governments, financial institutions, and related stakeholders to complement KUR financing with capacity-building programs, financial education, and digital transformation initiatives. Such integrated efforts are essential to maximize the role of KUR in driving sustainable regional economic growth in Pinrang Regency